The English language needs of biomedical science students at the University of Malaya / Usha Rani A/P S. Ganapathi - Ganapathi, Usha Rani (2012)
The Biomedical Science Programme in the Department of Molecular Medicine in the Faculty of Medicine, University Malaya offers an ESP course to students in their second year. This aim of this study was to establish the importance of the ESP course that the biomedical students are required to take in their second year and to find out to what extent the course fulfills the students’ needs to use English. The study explored the participants’ frequency of English use in a range of academic and non-academic activities as well as the kind of difficulties they face in using the English language within and outside their academic environment. The study used questionnaires to answer the two research questions: (1) What are the academic and non-academic activities which require biomedical students to use the English language and, 2) What difficulties do they have, if any, in the use of the English language in academic and non-academic situations. The findings of this study have clearly indicated that the participants need the ESP course to perform well in their field of study. The participants have to use the English language for listening, speaking, reading and writing in their academic context as English is an important medium of communication in biomedical work and research. The findings of this study will significantly guide the ESP course lecturer to further improve and re-align the course materials and the teaching focus with the English language needs of the biomedical students.